2012
DOI: 10.1088/0029-5515/52/12/123014
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of neoclassically predicted edge current density at ASDEX Upgrade

Abstract: Abstract. Experimental confirmation of neoclassically predicted edge current density in an ELMy H-mode plasma is presented. Current density analysis using the CLISTE equilibrium code is outlined and the rationale for accuracy of the reconstructions is explained. Sample profiles and time traces from analysis of data at ASDEX Upgrade are presented. A high time resolution is possible due to the use of an ELM-synchronisation technique. Additionally, the flux surface averaged current density is calculated using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 23 publications
7
49
0
Order By: Relevance
“…This suggests that electromagnetic filaments could be responsible also for bending magnetic field lines 10 , local modification of magnetic topology 12 or wider modification of the plasma column as suggested for example in the case of ASDEX-Upgrade. Here it has been found that the ELMs are associated with a reduction of the plasma radius hinting to a movement of the plasma outside the last close flux surface and to a redistribution of the edge current profile 13 . In the present paper we focus in particular on the direct measurement of turbulent filamentary structures current density, which can provide an efficient channel for current transport 14 .…”
Section: Introductionmentioning
confidence: 83%
“…This suggests that electromagnetic filaments could be responsible also for bending magnetic field lines 10 , local modification of magnetic topology 12 or wider modification of the plasma column as suggested for example in the case of ASDEX-Upgrade. Here it has been found that the ELMs are associated with a reduction of the plasma radius hinting to a movement of the plasma outside the last close flux surface and to a redistribution of the edge current profile 13 . In the present paper we focus in particular on the direct measurement of turbulent filamentary structures current density, which can provide an efficient channel for current transport 14 .…”
Section: Introductionmentioning
confidence: 83%
“…6 (b) it is useful to study the bootstrap current. With larger col-lisionality the bootstrap drive coefficients decrease [30]. However, this does not necessarily mean smaller bootstrap contribution to the edge current density.…”
Section: Normalized Pressure Gradientmentioning
confidence: 94%
“…In contrary, j boot can even increase slightly. Following the ideas in [30], a simple estimate can be made. Assuming constant pressure and proportionality between gradients and pedestal height, a change of the collisionality from 0.5 to 1.7 will influence the bootstrap current by less than 5%.…”
Section: Normalized Pressure Gradientmentioning
confidence: 99%
“…However, the strong edge variation of the pressure gradient and current density peak are only poorly reflected. Constraining the edge pressure profile leads to a much higher accuracy in the final equilibrium [12]. This requires high quality kinetic measurements, which at AUG are provided by electron cyclotron emission (ECE) [13], Thomson scattering [14,15], lithiumbeam emission spectroscopy [16,17], deuterium cyanide interferometry [18] and charge exchange recombination spectroscopy [19] diagnostics.…”
Section: Methodsmentioning
confidence: 99%